Use of ionic liquid for improvement of glucose yield for ethanol production - Lim, Wan Sin (2017)
Bioethanol production had become one of the popular alternative source of energy to reduce the consumption of fossil fuel based energy. Ionic liquid (IL) are of great interest as solvents for production of fuels from lignocellulosic biomass. The aim of this research is to determine the efficiency of ionic liquid, 1-butyl-3-methylimidazolium (BMIMCl) pretreatment on rice husk (Oryza sativa) for improvement of bioethanol production. The pretreatment was conducted by heating 5 % (w/w) rice husk in BMIMCl solution at 80 ℃ for 48 hours. Rice husk was regenerated by addition of water. The composition of rice husk before and after IL BMIMCl pretreatment were analysed using Technical Association of the Pulp and Paper Industry (TAPPI) test method. The structural changes were also observed and characterized using X-ray diffraction (XRD) and fourier transform infrared spectroscopy (FTIR). It was found that the regenerated rice husk was less crystalline and more high amorphous upon BMIMCl treatment which agreed with finding of XRD and FTIR. The total sugar yield before and after fermentation by saccharomyces cerevisiae was analysed using dinitrosalicyclic acid (DNS) method. The regenerated rice husk produces higher total sugar yield compared with untreated rice husk. Therefore, BMIMCl was effective in improvement of bioethanol production.